2011
DOI: 10.1103/physrevb.84.064514
|View full text |Cite
|
Sign up to set email alerts
|

Composite pairing in a mixed-valent two-channel Anderson model

Abstract: Using a two-channel Anderson model, we develop a theory of composite pairing in the 115 family of heavy fermion superconductors that incorporates the effects of f -electron valence fluctuations. Our calculations introduce "symplectic Hubbard operators": an extension of the slave boson Hubbard operators that preserves both spin rotation and time-reversal symmetry in a large N expansion, permitting a unified treatment of anisotropic singlet pairing and valence fluctuations. We find that the development of compos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…In the present context of QPI theory the microscopic origin of the unconventional superconductivity is not an issue. For CeCoIn 5 , various proposals based on spin fluctuation theory 17,18 and composite pairing 19 have been advanced.…”
Section: Introductionmentioning
confidence: 99%
“…In the present context of QPI theory the microscopic origin of the unconventional superconductivity is not an issue. For CeCoIn 5 , various proposals based on spin fluctuation theory 17,18 and composite pairing 19 have been advanced.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the key prediction of the composite pairing theory for a sharp NQR frequency shift upon entering the SC state 11,38 could not be verified.…”
Section: Discussionmentioning
confidence: 94%
“…Such a picture for the normal-state fluctuations in PuCoGa 5 would resemble, for example, the case of δ-Pu where the mixed-valence 5f states 12 are accompanied by well-defined spin fluctuations, as was recently revealed by inelastic neutron scattering 37 . An alternative theoretical approach puts forth a composite pairing mechanism, within the framework of a two-channel Anderson model 10,11,38 , aiming to provide an overarching microscopic description for heavy-fermion superconductivity. This theory predicts a sharp change in ν Q upon entering the SC state, due to redistribution of the f -electron charge within the unit cell 11,38 .…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Neutron inelastic scattering has failed to detect any sign of a resonance as found, for example, in the isostructural CeCoIn 5 compound [9], which also has d-wave symmetry, although the difficulty of performing these neutron experiments on Pu should not be overlooked. Recent theoretical efforts [10][11][12] have concluded that the driving mechanism for superconductivity is valence fluctuations. Electronic structure calculations combining the local-density approximation with an exact diagonalization of the Anderson impurity model [13] show an intermediate 5f 5 − 5f 6 -valence ground state and delocalization of the 5f 5 multiplet of the Pu atom 5f shell.…”
Section: Introductionmentioning
confidence: 99%